United States health plan cancer concerns in 2019 - Brook, Richard A. (J Drug Assess, 2019)
Background: Cancer care is shifting from chemotherapy to more effective targeted immunotherapies. New therapies, some existing therapies with expanded indications (including maintenance) and many therapies with price increases require re-evaluation. Many agents are handled through specialty pharmacies (SPs). Aims: The onslaught of newer oncology therapies have increased economic concerns. Coinsurance and benefit limitations can leave patients “financially toxic” but produce outcomes that justify coverage. Efforts utilizing immuno-oncology (chimeric antigen receptor [CAR]-T therapy and tumor-agnostic treatments) directed at molecular signatures are revolutionizing chemotherapy. There are ≥165 CAR-T therapies in trials, three marketed tumor-agnostic drugs used in combination with other oncology agents. The objective was to determine oncology areas of most concern to managed care plans. Methods: An online survey invitation was sent to officers of US healthplans and PBMs covering: officer and plan information, cancer ranking (lowest = 1 to 13 = highest), copays, benefit design, cancer management, and concerns today and in 5 years from budgetary and medical points of view (POVs). The results were compared with prior surveys. Results: Eighty-five respondents completed the survey. Respondents served on a variety of committees from plans covering multiple member types including Commercial FFS = 41%, Medicaid = 70%, IDN = 57%, HMO/PPO = 22% and Employer self-funded = 22%. Oncology was the third highest ranked SP – condition covered 85.3%↑3.5% and 51.2% of respondents reported they participated in oncology accountable care/disease management organizations; 88.5% covered oncology genomic tests; 13.8% used value-based contracting for oncology. The cancers most concerning were: lung = 11.1, breast = 10.8, colon and rectal = 9.7, prostate = 8, melanoma = 7.6, leukemia = 7.4, myeloma = 7.4, non-Hodgkin’s lymphoma (NHL) = 7.3, pancreatic = 5.7, kidney = 5.1, endometrial = 4.9, bladder = 4.7 and thyroid = 2.9. Cancer management is: 61.2%↓7.7% sometimes leave specialists alone, always follow NCCN guidelines 67.4%↑ 6%, sometimes follow other guidelines or pathways 81.3% and 53.1% sometimes follow internal protocols. Oncology outranked other newer expensive therapies as a financial concern – combination oncology therapy was ranked first = 68%, CAR-T second 35.3%. Cancer was consistently a top concern from medical care (47.2% today, 50% in 5 years) and budgetary (50% today, 60.9% in 5 years) POVs. Conclusions: Improvements in oncology agents and the growth of immuno-oncology have implications that require plans to focus on benefit design, adopt newer agents and utilize pathways.